Augmented Reality-Based Smart Digital Interactive Media to Enhance High School Students Socio-Scientific Reasoning in Chemistry - Kartyka Nababan; Dina Mariana Siregar; Victor Tarigan; Leony Sanga Lamsari Purba; Renta Renta (Jurnal Pijar MIPA, 2025)
The persistent difficulty in connecting abstract chemistry concepts with real-world socio-scientific issues highlights the need for well-designed digital learning innovations. This study aimed to develop and evaluate an Augmented Reality–based Smart Digital Interactive Learning Media (Smart-DIL) to support senior high school students’ socio-scientific reasoning and 21st-century skills. The study employed a Research and Development (R&D) approach, utilising the ADDIE model, which encompasses the stages of Analysis, Design, Development, Implementation, and Evaluation. The evaluation stage involved a limited product try-out in authentic classroom settings to examine the validity, practicality, and effectiveness of the developed media. Data were collected from 72 eleventh-grade science students using the Socio-Scientific Reasoning Test (SSRT), the 21st Century Skills Scale (21CSS), classroom observations, interviews, and analysis of digital learning artifacts. Expert judgment and user response questionnaires were used to assess product feasibility and usability. The results indicate that Smart-Dil demonstrates high validity and practicality, as reflected in expert validation scores and positive responses from teachers and students. Evaluation evidence further shows that the implementation of Smart-Dil is associated with meaningful improvements in students’ socio-scientific reasoning, particularly in analyzing scientific evidence and constructing evidence-based arguments. In addition, positive developments were observed across all dimensions of 21st-century skills, including critical thinking, creativity, collaboration, and communication. These findings support the integration of Augmented Reality technology within a socio-scientific pedagogical framework, as conceptualized in the proposed TPACK–SSI model. The study concludes that Smart-Dil represents a feasible, practical, and effective learning media product that can help bridge abstract chemistry concepts with authentic societal contexts. The results provide important implications for the development of future digital learning media grounded in Research and Development approaches.